Science Pre-service Teachers’ TPACK, Readiness, Self-Efficacy, and Challenges Toward Online Teaching Internship - Espinosa, Renz John Bryan C.; Gilbuena, Sheena Marie D.; Ibale, Tyra Lee L.; Inot, Clifford M.; Laurito, Ryan A.; Sanchez, Joje Mar Perino (Jurnal Penelitian dan Pembelajaran IPA, 2024)
This embedded mixed method research study examined the pre-service teachers’ (PST) technological, pedagogical, and content knowledge (TPACK) towards their readiness and self-efficacy considering their foresight challenges in online Science teaching internship.  It is revealed that PSTs have adequate levels of expertise in TPACK, ranging from moderate to ample in all areas, interconnected with their reflected moderate levels of readiness and self-efficacy. The results of partial least squares-structural equation modeling (PLS-SEM) showed that out of all areas of TPACK, only the pedagogical knowledge (PK) manifested a significant relationship with the PSTs’ readiness and self-efficacy in the online teaching internship.  PSTs were challenged by their issues, uncertainties toward teaching training, complicated roles of teacher interns, concerns on TPACK, and external threats.  In conclusion, the PSTs are proficient and prepared enough to perform an upright Science lesson delivery and have excellent classroom management skills, albeit with some challenges as teachers in online education.  Moreover, a pre-service science teacher who is well-oriented and well-prepared is already on the journey to meet accomplishment and proficiency.  Training on online pedagogies and mentorship is recommended.